Analisis Kontribusi Biaya Pakan dan Biaya Operasional Berbasis PSAK 241 Terhadap Keuntungan Peternakan Domba (Studi Kasus Aba Farm, Ujung Berung, Kabupaten Bandung) - Rindu Aulia Ayum; Faridatus Sa'adiyah; Silmi Fitriani; Muhammad Hamiz Al-Qowiyy; Yati Nurhajati (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the condition of feed cost, operational costs, and profit at ABA Farm, a sheep fattening enterprise located in Ujung Berung, Bandung Regency, and to examine the contribution of feed cost and operational costs to business profit within the framework of PSAK 241 Agriculture. This research uses a descriptive qualitative approach with a single-case case study method based on secondary data. Data were collected through internal financial documents only, without primary data from interviews or direct observation, and analyzed using the Miles and Huberman interactive model. The results show that during the period from August 2025 to June 2026, ABA Farm recorded total sheep sales of IDR 351,764,150, with total livestock purchase costs of IDR 200,083,578 and total operational costs of IDR 113,092,292, resulting in a net profit of IDR 38,588,281, or a net profit margin of 10.97%. Feed cost was the largest operational cost component (65.31%), indicating that feed cost contributes substantially to business profit, although the available data only capture total feed cost rather than the unit feed price. Other operational costs, such as labor wages, slaughter fees, delivery costs, and vitamin costs, also contributed to margin erosion, particularly as unit cost rates increased in more recent fattening cycles. Overall, feed cost and operational costs absorbed nearly 89% of total sales, making the integrated management of both cost components a key factor in sustaining the profitability of the sheep fattening business. From the perspective of PSAK 241 (Agriculture), the sheep raised by ABA Farm meet the criteria for biological assets; however, documentation regarding the acquisition cost of unsold livestock needs improvement to ensure that the recording of biological assets better aligns with PSAK 241 standards. As a single-case descriptive study, these findings are not intended to be generalized.